Therapeutic Efficacy of Sorafenib in Patients with Hepatocellular Carcinoma Recurrence After Liver Transplantation: A Systematic Review and Meta-Analysis - Li, Zhao; Gao, Jie; Zheng, ShengMin; Wang, Yang; Xiang, Xiao; Cheng, Qian; Zhu, Jiye (Turkish Journal of Gastroenterology, 2021)
Background/Aims: Hepatocellular carcinoma (HCC) recurrence is still threatening patient survival after liver transplantation (LT). The efficacy and safety of sorafenib in the setting of post-LT recurrence are still equivocal. This study aim to disclose the efficacy and safety profile of sorafenib in treating post-LT HCC recurrence. Materials and Methods: Electronic databases were searched to retrieve relevant publications suitable for inclusion. Data from 23 studies containing 411 patients were analyzed. The primary outcome of interest was 1-year survival rate after sorafenib treatment, and the secondary endpoints included median overall survival (OS), time to progression (TTP), treatment response, and adverse events. Results: Patients with HCC recurrence after LT treated with sorafenib achieves a 1-year survival rate of 56.8%, with a median OS of 12.8 months and a median TTP of 6.0 months. Univariate logistic regression analysis showed that male gender (P = 0.048), TTP (P = 0.021), median duration of sorafenib (P = 0.021), diarrhea (P = 0.027), fatigue (P = 0.044), and partial response (P = 0.026) were associated with a better 1-year survival rate. In addition, sorafenib exerted significant superior effect on OS compared with best supportive care in the setting of untreatable post-LT HCC recurrence.Conclusion: Based on the results of this meta-analysis, sorafenib therapy seems to be safe and feasible and possess with survival benefit in patients with post-LT HCC recurrence. However, prospective randomized controlled trials with larger sample sizes and more rigorous study design are required to confirm the efficacy of sorafenib.